2000
DOI: 10.1177/074873040001500204
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Innervation of Calbindin-D28K Cells in the Hamster Suprachiasmatic Nucleus: Ultrastructural Characterization

Abstract: The authors have described a subregion of the hamster hypothalamic suprachiasmatic nucleus (SCN) containing cells that are immunopositive for the cytosolic calcium-binding protein, Calbindin-D 28K (CaBP). Several lines of evidence indicate that this region may constitute the site of the pacemaker cells that are responsible for the regulation of circadian locomotor rhythms. First, 79% of the CaBP-immunoreactive (ir) neurons express Fos in response to photic stimulation, indicating that they are close to or part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
(38 reference statements)
0
73
1
Order By: Relevance
“…This region is crucial for the generation of circadian rhythmicity, as shown by the loss of circadian rhythms in behavior (locomotor activity, drinking, gnawing) and circulating concentrations of hormones (melatonin and cortisol) in hamsters after discrete lesions of this area (LeSauter and Silver, 1999;Kriegsfeld et al, 2004b). Also, the calbindin subnucleus receives direct retinal innervation (Bryant et al, 2000) and mediates photic phase shifts, as demonstrated by the finding that intracerebroventricular administration of calbindin antisense oligonucleotides attenuates light induction of Per1 mRNA expression in the SCN and circadian phase shifts (Hamada et al, 2003). The present identification of 5-HT 7 receptor mRNA within the calbindin subnucleus supports other findings that post-synaptic 5-HT 7 receptors in the SCN modulate the effects of serotonergic agonists on responses to light or to glutamate, the major neurotransmitter released by the retinohypothalamic tract that innervates the SCN (Ying and Rusak, 1997;Quintero and McMahon, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This region is crucial for the generation of circadian rhythmicity, as shown by the loss of circadian rhythms in behavior (locomotor activity, drinking, gnawing) and circulating concentrations of hormones (melatonin and cortisol) in hamsters after discrete lesions of this area (LeSauter and Silver, 1999;Kriegsfeld et al, 2004b). Also, the calbindin subnucleus receives direct retinal innervation (Bryant et al, 2000) and mediates photic phase shifts, as demonstrated by the finding that intracerebroventricular administration of calbindin antisense oligonucleotides attenuates light induction of Per1 mRNA expression in the SCN and circadian phase shifts (Hamada et al, 2003). The present identification of 5-HT 7 receptor mRNA within the calbindin subnucleus supports other findings that post-synaptic 5-HT 7 receptors in the SCN modulate the effects of serotonergic agonists on responses to light or to glutamate, the major neurotransmitter released by the retinohypothalamic tract that innervates the SCN (Ying and Rusak, 1997;Quintero and McMahon, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…7. This figure indicates that the retinal (Silver et al, 1996;Bryant et al, 2000), NPY and 5-HT afferent pathways, as well as the ventral VIP cells, contact all or nearly all the CalB cells.A caveat in the present study is that only somatic appositions were counted. While the varicosities terminating onto the cell bodies, on large fibers, or axon hillocks near the cell bodies are quite clear, it is very difficult to determine whether varicosities seen on fine fibers are appositions, fibers crossing each other, or small artifacts resulting from the immunocytochemistry procedure.…”
mentioning
confidence: 82%
“…All these cells may be part of the light entrainment mechanism in hamsters. CalB (Bryant et al, 2000) and GRP (Aioun et al, 1998) cells receive retinal terminals and presentation of a light pulse during the night induces c-Fos in about 80% of the CalB cells (Silver et al, 1996), 78% of the GRP cells and 60% of the VIP cells (Aioun et al, 1998). It is also known that administration of GRP (McArthur et al, 2000) or coadministration of VIP, peptide histidine isoleucine and GRP (Albers et al, 1991) induce phase-dependent resetting of the SCN that resembles the lightinduced phase response curve.…”
Section: Colocalization Of Peptides In the Calb Subnucleusmentioning
confidence: 99%
See 2 more Smart Citations